تصميم منظومة ري دفقي كتطوير لمنظومات الري بالتنقيط - لمى شعبان (Tishreen University, 2019)
The aim of the study is to develop a drip irrigation system by using various lengths of small pores, polyethylene pipes (PE) which have internal diameters instead of using the drippers. Thus, to effectively reduce the risk of the potential clogging in the drippers. Moreover, to achieve equal inflows along with the appropriate head for the entire system. By applying this system which is referred to as the inflow irrigation system, using different lengths of the pipes and constant diameters, we will be able to achieve a value of EU= 100% for the entire system. The length of the pipes is determined based on the required head values at the end of the laterals. The inflow irrigation system runs by gravity. The system consists of a reservoir which is designed to achieve the required head subsequently to achieve the desired inflow. This system is designed taking into consideration the frictional head losses. A logarithm is built using VBA language in order to compute the required lengths of the tubes, the number of coils in each tube as well as the required head at the inlet of the lateral HT. In this study the algorithm has been developed, in order to design a typical irrigation subunit using polyethylene tubes taking into consideration the following requirements: -                      The area to be irrigated -                      The spacing between the plants -                      The slope of the soil -                      The inclination of the network, and -                      The diameters of the used tubes     يعتمد الري الدفقي على إيصال دفقات المياه إلى جذور النباتات مباشرة وفق ضاغط وغزارة معينة تحقق الحاجة المائية للمحصول، وبدأ حديثا استخدام أنظمة الري بالتنقيط على نطاق واسع من العالم   رغم العقبات والقيود التي تواجه هذه الأنظمة. لعل الانسدادات وعدم التجانس في الريات لفترات طويلة أبرز هذه العقبات والمشاكل، على الرغم من تركيب معدات تصفية والفلترة  لحل مشكلة الانسدادات، غير أنها لم تتمكن من علاج هذه المشكلة حتى الآن. إن هدف هذه الدراسة هو تطوير منظومات الري بالتنقيط من خلال تصميم نموذج لمنظومة ري دفقي باستخدام أنابيب مفتوحة مصنوعــة من مادة البولـي أثيليـن عوضاً عن النقاطات، هكذا نحد وبشكل فعال من مشاكل الانسداد ونستطيع الحصول من خلالها على معدلات متجانسة للدفقات على كامل المنظومة بما يتوافق مع الضاغط المناسب والواجب تأمينه للحصول على الغزارة (الدفقة) المطلوبة، فمن خلال استخدام الأنابيب المفتوحة مختلفة الأطوال وذات القطر الثابت نحصل على معامل تجانس (EU=100%) على كامل المنظومة ويتم تحديد أطوال أنابيب الدفقات بالاعتماد على الضاغط عند مدخل أنبوب الدفقة. تعمل منظومة الري الدفقي اعتماداً على نظام الجاذبية الأرضية حيث يتم تصميم خزان مناسب يحقق  الضاغط الواجب تأمينه لعمل المنظومة وفق الغزارة المطلوبة. يتم تصميم منظومة الري الدفقي اعتماداً على الضياعات باستخدام معادلات دارسي فايسباخ وسنقوم بوضع برنامج اعتماداً على لغة (VBA) لحساب الأطوال المناسبة للأنابيب المفتوحة إضافة للضاغط المطلوب تأمينه للحصول على دفقات متجانسة وفق المعطيات المطلوبة (المساحة المروية - التباعد بين النباتات - انحدار الأرض) وبالتالي ميل أنابيب الشبكة وأقطار الأنابيب المستخدمة.